Persuasion Act in the Proposal Movie - Soedjarwo, Gabriella Novianty (State institute of islamic studies salatiga, 2020)
The act of persuasion happens anywhere and anytime. When we need a help, we persuade other to do what we need. In order to have a successful persuasion, we apply certain strategy. This pragmatic paper wants to analyse the effective strategies in order to have an effective persuasive acts. Pragmatics is chosen as the method since the analysis is about the language used in certain context, in this case persuasion. This paper elaborates how certain speech acts can help the speaker to perform persuasion successfully. Besides, the researcher also analyses how the attempts of persuading violate certain maxims stated by Grice. The researcher took a movie entitled The Proposal (2009) as the data since it shows how the main characters apply certain speech acts and strategies in order to achieve effective persuasion. In this movie, Margaret and Andrew are trying to persuade each other in order to get different advantages through faking marriage. The researcher takes the dialogue of those two characters as the data. Then, the data was analysed using speech act theory, implicature, and language function theory on persuasion. The result of the study is the successful persuasion relies on using appropriate speech act, flouting the maxim of quantity, and applying good persuasive strategy. Key words: Persuasion, Speech Act, Maxim, Strategy